Coinfection in SARS-CoV-2 Infected Children Patients - Ayşe Karaaslan; Ceren Çetin; Yasemin Akın; Serap Demir Tekol; Elif Söbü; Recep Demirhan (Journal of Infection in Developing Countries)
Introduction: The aim of this study is to determine the coinfections with other respiratory pathogens in SARS-CoV-2 infected children patients in a pediatric unit in Istanbul.